Numerical Investigation of Heat and Mass Transfer in Radiative Magnetohydrodynamic Flow with Chemical Reaction - Sulochana, C.; Kumar, M. K. Kishor (International Journal of Advanced Science and Technology, 2016)
Numerical investigation is carried out to analyze the heat and mass transfer in magnetohydrodynamic flow over a stretching sheet in the presence of thermal radiation and chemical reaction. The governing equations are transformed as ordinary differential equations using self suitable transformations, further these equations are solved numerically using shooting technique. The influence of pertinent parameters namely, magnetic field parameter, thermal radiation parameter, chemical reaction parameter, thermal and mass Grashof numbers etc., on velocity, temperature and concentration fields are discussed with the assistance of graphs. Numerical results are presented to discuss the behaviour of friction factor along with heat and mass transfer rate. Results shows that thermal radiation parameter have tendency to enhance the thermal boundary layer thickness.